Subjective Birth Experience and Person-Centred Care in Obstetrics: Study Protocol of the Prospective Mixed-Methods Research Project RESPECT - Vollert, Bianka; Schurig, Nina; Zieß, Vanessa; Weise, Victoria; Seefeld, Lara; Göbel, Ariane; Birdir, Cahit; Wimberger, Pauline; Garthus-Niegel, Susan (Geburtshilfe und Frauenheilkunde, 2025)
The interdisciplinary research project RESPECT (A Prospective Mixed-Methods-REsearch Project on Subjective Birth Experience and PErson-centred Care in ParenTs and Obstetric Health Care Staff) aims to investigate the subjective birth experience of (expectant) parents in Germany and associated factors before, during, and after childbirth, including care-related aspects such as person-centred care and mistreatment during childbirth. In addition, the perspective of obstetric health care staff regarding their role in parents’ subjective birth experience and person-centred care in obstetrics are explored.RESPECTPARENTS is a prospective cohort study targeting a community sample of expectant parents in the Dresden area with four assessment points from pregnancy to 24 months postpartum using online questionnaires and a structured telephone interview. Applying a mixed-methods approach, the main study is complemented by a sub-study with parents (RESPECTPARENTS-TALK) and an additional study branch with obstetric health care staff (RESPECTSTAFF), both using qualitative interviews.In this study protocol, the theoretical background, methods, and first results regarding sociodemographic and birth-related variables of the sample (N = 2424 participants including n = 1693 expectant mothers/birthing parents and n = 731 partners) are presented and discussed.The data will provide meaningful insights into parents’ subjective birth experience and health-related effects over time, considering the perspectives of both parents and the obstetric health care staff. The findings can contribute to the development of strategies to improve obstetric health care according to the latest WHO recommendations and the German national health goal “Health around childbirth”, and thus to prevent traumatic birth experiences.
Keywords: subjective birth experience; person-centred care; obstetric violence/mistreatment; parental mental health; mixed-methods